Decomposition of factors associated with housing material inequality in under-five deaths in low and middle-income countries (2022)
Background: Low-and Medium-Income Countries (LMIC) continue to record a high burden of under-five deaths (U5D). There is a gap in knowledge of the factors contributing to housing materials inequalities in U5D. This study examined the contributions of the individual- and neighbourhood-level factors to housing materials inequalities in influencing U5D in LMIC. Methods: We pooled data from the most recent Demographic and Health Surveys for 56 LMIC conducted between 2010 and 2018. In all, we analysed the data of 798,796 children living in 59,791 neighbourhoods. The outcome variable was U5D among live births within 0 to 59 months of birth. The main determinate variable was housing material types, categorised as unimproved housing materials (UHM) and improved housing materials (IHM) while the individual-level and neighbourhood-level factors are the independent variables. Data were analysed using the Fairlie decomposition analysis at α = 0.05. Results: The overall U5D rate was 53 per 1000 children, 61 among children from houses built with UHM, and 41 among children from houses built with IHM (p < 0.001). This rate was higher among children from houses that were built with UHM in all countries except Malawi, Zambia, Lesotho, Gambia, Liberia, Sierra Leone, Indonesia, Maldives, Jordan, and Albania. None of these countries had significant pro-IHM inequality. The factors explaining housing inequalities in U5D include household wealth status, residence location, source of drinking water, media access, paternal employment, birth interval, and toilet type. Conclusions: There are variations in individual- and neighbourhood-level factors driving housing materials inequalities as it influences U5D in LMIC. Interventions focusing on reducing the burden of U5D in households built with UHM are urgently needed.